A Design for barrier-free interior design standard guidelines with focus on retail apparel stores and wheelchair-user experience Angela Ysobelle M. Titular ; Pamela B. Aquino, adviser. - Titular, Angela Ysobelle M.; Aquino, Pamela B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2020)
The study analyzed the wheelchair user's shopping experience and the selected existing retail apparel stores in the Philippines in order to draft proposed barrier-free interior design standard guidelines for retail apparel stores. These guidelines were made using theories such as accessibility, anthropometrics, universal design. The study used a qualitative research approach where the theories above were applied to analyze the data gathered. Seven (7) wheelchair user customers of retail apparel stores and nine (9) retail apparel store operators, and five (5) retail apparel stores volunteered to participate and were surveyed in this study. The tools used were online surveys, photographic equipment, and computer-aided design (CAD) in the collection and analysis of the data. The results showed that the retail apparel stores included and referenced in this study do not have in place the needed accessibility in their interior design, despite the claims of the retail apparel store operators. Wheelchair-user customers stated their issues and problems regarding reachability and mobility within the retail apparel stores they have visited in the past. Retail apparel store operators are also unaware that their stores do not meet the requirements for the accessibility of wheelchair users. With the data gathered and the use of theories such as accessibility, anthropometrics, and universal design, the researcher has drafted a proposed barrier-free interior design standard guidelines for retail apparel stores that focuses on the wheelchair-user experience. For further improvements, the researcher recommended to collect a bigger sample of wheelchair-user customers and retail apparel store operators. It is also recommended to include commercial space owners/lessors in the study as they can influence the implementation of future design standards in the retail apparel stores that occupy their commercial space.
Thesis Classification: F (Available for Public)
Thesis
Includes bibliographical references and appendices.
Keywords: Stores, Retail -- Barrier-free design -- Philippines